Sounds of music: exploring consumers' musical engagement. Issue 6 (12th September 2016) - Hollebeek, Linda D.; Malthouse, Edward C.; Block, Martin P.
Abstract : Purpose: Although "engagement" is receiving increasing attention in the marketing literature, the characteristics and dynamics characterizing this concept in specific contextual conditions, including consumers' selection of particular music and ensuing music-related behaviors, remain nebulous to date. This study aims to develop the concept of consumers' musical engagement (ME) and explore it within a broader nomological network of conceptual relationships. Design/methodology/approach: To investigate the research gap, the authors deploy a survey sampling 2, 498 US-based adults to develop and confirm a 25-item ME scale. The authors also test their scale in a broader nomological network of specific theoretical relationships using regression and mediation modeling. Findings: The authors identify three ME factors, namely, social identity, transportive and affect-inducing engagements. The authors find ME to exhibit a nonlinear effect on music consumption with increasing returns. Although both social identity and transportive experiences represent significant predictors of music consumption, the effect of affect-inducing experience is non-significant. Further, the social identity experience has a significantly greater association with music consumption than the transportive experience. Research limitations/implications: This paper provides a conceptualization and an associated diagnostic tool for ME, in addition to initial insight into the role of ME in a broader nomological network of conceptual relationships. Based on the identified research limitations, the authors also provide key future research directions for ME. Practical implications: The insight attained into ME may be used to underpin the design, implementation and evaluation of managerial ME-based tactics and strategies in the music industry. In particular, the authors find that successful appeals to consumers' social identity engagement are a significant driver of increased future music consumption. The authors provide a number of managerial recommendations to develop this particular ME dimension. Originality/value: This paper provides an ME conceptualization and an associated scale and explores ME within a broader nomological network of theoretical relationships. The authors also draw key implications from these analyses.